Heat Shock Factor Genes of Tall Fescue and Perennial Ryegrass in Response to Temperature Stress by RNA-Seq Analysis - Wang, Yan; Dai, Ya; Tao, Xiang; Wang, Jia-Zhen; Cheng, Hai-Yang; Yang, Hong; Ma, Xin-Rong (Frontiers in Plant Science, 2016)
Heat shock factors (Hsfs) are important regulators of stress-response in plants. However, our understanding of Hsf genes and their responses to temperature stresses in two Pooideae cool-season grasses, Festuca arundinacea and Lolium perenne, is limited. Here we conducted comparative transcriptome analyses of plant leaves exposed to heat or cold stress for 10 h. Approximately, 30% and 25% of the genes expressed in the two species showed significant changes under heat and cold stress respectively, including subsets of Hsfs and their target genes. We uncovered 74 Hsfs in F. arundinacea and 52 Hsfs in L. perenne, and categorized these genes into three subfamilies, HsfA, HsfB, and HsfC based on protein sequence homology to known Hsf members in model organisms. The Hsfs showed a strong response to heat and/or cold stress. The expression of HsfAs was elevated under heat stress, especially in class HsfA2, which exhibited the most dramatic responses. HsfBs were upregulated by the both temperature conditions, and HsfCs mainly showed an increase in expression under cold stress. The target genes of Hsfs, such as heat shock protein (HSP), ascorbate peroxidase (APX), inositol-3-phosphate synthase (IPS), and galactinol synthase (GOLS1), showed strong and unique responses to different stressors. We comprehensively detected Hsfs and their target genes in F. arundinacea and L. perenne, providing a foundation for future gene function studies and genetic engineering to improve stress tolerance in grasses and other crops.